Poesia e transcendência no Quatro Quartetos, de T. S. Eliot - Santos, Alcides Cardoso dos [UNESP] (My University, 2012)
Considered by critics to be the highest point in T. S. Eliot’s poetic production, the Four Quartets carry out a poetical reflection on time under the direct influence of Henri Bergson’s philosophy. What we would like to show in this article is how Eliot’s poetical use of Bergson’s concept of durée makes it possible for the poet to articulate poetry and thought in a unique combination which is peculiar to Eliot’s poetry. The peculiarity of such combination poetry-thought in the Four Quartets, this is the second point we would like to show, fundamentally involves a religious-poetical-philosophical syncretism that can be seen already in Eliot’s first poems, but which gets full expression in the Four Quartets.

Artigo publicado originalmente no número 8 (julho 2012) da Revista FronteiraZ e republicado no número 9 (2012) da mesma revista em número especial com os artigos representativos de cada volume desde a sua criação em 2008.
Keywords: Four Quartets; Eliot; Poetry; Thought; Syncretism; Quatro Quartetos; Eliot; Poesia; Pensamento; Sincretismo